Extraosseous Osteosarcoma of the Esophagus: A Case Report - Wegner, Rodney E. (Hindawi Publishing Corporation, 2010)
Extraosseous osteosarcoma (EOO) is a malignant mesenchymal neoplasm that is located in the soft tissues without direct attachment to the skeletal system and that produces osteoid, bone, or chondroid material. EOO is an extremely rare disease, accounting for only 1% of soft tissue sarcomas, and typically presents in either an extremity or the retroperitoneum. This paper presents the case of a 45-year-old Caucasian male with extraosseous osteosarcoma of the esophagus.